Estimation of Intraoperative Stimulation Threshold of the Facial Nerve in Patients Undergoing Microvascular Decompression - Feroze, Rafey A.; McDowell, Michael M.; Balzer, Jeffrey; Crammond, Donald J.; Thirumala, Partha; Sekula, Raymond F., Jr. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Facial weakness can result from surgical manipulation of the facial nerve. Intraoperative neuromonitoring reduces functional impairment but no clear guidelines exist regarding interpretation of intraoperative electrophysiological results. Most studies describe subjects with facial nerves encumbered by tumors or those with various grades of facial nerve weakness. We sought to obtain the neurophysiological parameters and stimulation threshold following intraoperative facial nerve triggered electromyography (t-EMG) stimulation during microvascular decompression for trigeminal neuralgia to characterize the response of normal facial nerves via t-EMG.Methods Facial nerve t-EMG stimulation was performed in seven patients undergoing microvascular decompression for trigeminal neuralgia. Using constant current stimulation, single stimulation pulses of 0.025 to 0.2 mA intensity were applied to the proximal facial nerve. Compound muscle action potentials, duration to onset, and termination of t-EMG responses were recorded for the orbicularis oculi and mentalis muscles. Patients were evaluated for facial weakness following the surgical procedure.Results Quantifiable t-EMG responses were generated in response to all tested stimulation currents of 0.025, 0.05, 0.1, and 0.2 mA in both muscles, indicating effective nerve conduction. No patients developed facial weakness postoperatively.Conclusions The presence of t-EMG amplitudes in response to 0.025 mA suggests that facial nerve conduction can take place at lower stimulation intensities than previously reported in patients with tumor burden. Proximal facial nerve stimulation that yields responses with thresholds less than 0.05 mA may be a preferred reference baseline for surgical procedures within the cerebellopontine angle to prevent iatrogenic injury.
Keywords: trigeminal neuralgia; stimulation threshold; t-EMG; CMAP